Percutaneous Direct Puncture Embolization for Superficial Craniofacial Arteriovenous Malformation - Ou, Chang-Hsien (Centauro S.r.l., 2008)
Endovascular embolization for craniofacial arteriovenous malformation has been used as preoperative adjuvant devascularization or as definitive therapy. However, because the vascular network is complex, embolization via arterial access may be ineffective, risky, incomplete or technically difficult. The purpose of this report is to describe our experience of percutaneous direct venous pouch puncture embolization. Four patients with craniofacial AVMs were treated with direct puncture embolization via injection of NBCA. After the selective transarterial angiogram, the lesions were directly punctured in the venous pouch under a road map angiogram. A glue mixture was injected, and post-embolization angiograms revealed that in all patients, the lesions had been completely obliterated without complication. Percutaneous direct puncture embolization is an effective, time saving and safe technique for the superficial craniofacial AVM with prominent venous pouch.